Optimization of Ganoderma lucidum Growth Contributing Concentration Gradient of Substrate Derived from Pine Forest Waste (International Journal of Food and Nutritional Sciences, 2022)
Environment deterioration can be control by the suitable various techniques by use of agro forest wastes as supplements. These substance derived from agriculture & forest trashes contains macro or micro nutrients for new plant growth in the field of biotechnology. some macro fungus like mushrooms use these trashes in gradient conc. mix with the change in growth by substrate mix ratio. Most of the forest Himalayan region it contains maximum trees of deodar , pine trees and the forest ground is covered with their shreds parts like their leaves, stems, branches, wood chips, pollen grains, cones etc .At the time of maturity maximum fall takes place cause thick covering sheets attracts fires in it this leads to cause forest fires .It caused destruction to flora and fauna lives inside the forests. The fungi commonly known as Ganoderma lucidum form as bridge provide by nature to balance the plant waste by their different lignocelluosic and ligninolytic enzymes activity with respect to conc. gradient and substrate mix . These leaves wastes are consumed by mushrooms miracle to decrease the calamities, act as natural scavengers. In this observations includes evaluation of Ganoderma lucidum on pine waste leaves, wood bark, cone bundles etc. The minimum concentration test is carried out with the zone of exhibition (ZOE). The outer covering of pine cones, leaves are very rigid take a time to degrade in environmental condition ,so for cultivation purpose substrate mix preparation these forest pine waste is pretreated by cutting, chopping ,grinding ,water extraction .To evaluate the observation cone and pine leaves mixture shows max growth in plates than 40,30,20,10µl conc. by showing zones in media. The observation shows the mushroom enzymatic activity of the mushroom with minimum concentration of waste mixture substrate for yield. The pine forest waste shows the higher growth rating in pine leaves & cone mix substrate(PLCD) than pine leaves mix substrate30%(PLSC) than pine leaves mix substrate 20%(PLSB) than pine leaves mix substrate10% (PLSA) than sawdust without any mixture(SAWD).as considering the BE of Ganoderma lucidum show different in different conc. BE is higher in PLCD then PLSC and lower in (SAWD) .The Biological efficiency of PLCD is 42.5%and PLSC 38.0% is near by then others after treatments. But the pine leaves are easily available in forest which are shredded by trees without cutting pine trees with less damage to forest . The wood chips and cones are not in large quantities they are less amount in forest than leaves .the reishi is cultivated by using local forest waste by products as substrates. The best mycelia growth and colonization were recorded mix with supplements and used as substrate for the growth of reishi .the PLSC mix show nearby in growth and yield of fruiting body. So PLSC is used in place of PLSD for economical efficient growth yield.